2020
DOI: 10.1186/s12872-020-01692-x
|View full text |Cite
|
Sign up to set email alerts
|

Weekly variation in markers of cardiometabolic health – the possible effect of weekend behavior – a cross-sectional study

Abstract: Background Adolescents’ health-related behavior varies from weekday to weekend. Only few studies, however, have examined to which degree such variation will affect markers of cardiometabolic health. Therefore, the primary aim of this study is to examine if markers of cardiometabolic health differ between different days of the week in adolescents. Methods This cross-sectional school-based study included up to 581 participants, 11–17 years old. Markers of metabolic health were insulin, glucose, triglyceride, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…In a previous study of Danish adults, we found higher fasting insulin concentrations on Mondays compared to the rest of the weekdays combined ( 10 ). The observed higher fasting insulin concentrations among men and the trend toward higher triglyceride concentrations on Mondays compared to other weekdays in this study are also in line with a previous study of 581 adolescents, showing a declining trend across the week in concentrations of plasma glucose, insulin, and serum triglycerides ( 12 ). Another study in children aged 8 to 11 years found higher insulin resistance and higher concentrations of triglycerides on Mondays compared to Friday ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In a previous study of Danish adults, we found higher fasting insulin concentrations on Mondays compared to the rest of the weekdays combined ( 10 ). The observed higher fasting insulin concentrations among men and the trend toward higher triglyceride concentrations on Mondays compared to other weekdays in this study are also in line with a previous study of 581 adolescents, showing a declining trend across the week in concentrations of plasma glucose, insulin, and serum triglycerides ( 12 ). Another study in children aged 8 to 11 years found higher insulin resistance and higher concentrations of triglycerides on Mondays compared to Friday ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, sex differences in fasting glucose and insulin concentrations in general is a well-known phenomenon ( 22 , 23 ). In line with this, a study in adolescents found higher variation in insulin across the week in boys than in girls ( 12 ). This sex difference may suggest that (1) men have another weekend behavior than women, (2) weekend behavior is acutely affecting metabolism stronger in men than women, or (3) it is a spurious finding caused by, for example, residual confounding.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…For example, a reliable indicator of cardiometabolic health is total cholesterol/HDL cholesterol, which should be measured in future experiments [ 25 ]. Additionally, insulin, glucose, triglycerides, and LDL cholesterol are all great markers of cardiometabolic health that can be measured in the future [ 26 ].…”
Section: Reviewmentioning
confidence: 99%